2019
DOI: 10.2298/pac1903257b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molar ratio on dielectric, ferroelectric and magnetic properties of Co0.5Mg0.5Fe2O4/Ba0.85Sr0.15TiO3 composite ceramics

Abstract: In the present work, Co 0.5 Mg 0.5 Fe 2 O 4 /Ba 0.85 Sr 0.15 TiO 3 (CMFO/BST) composite ceramics with different molar ratios (1:1, 1:2, 1:4, 1:6 and 1:8) were prepared by sol-gel method and sintered at 1150°C. The effects of molar ratio on the structure, dielectric and multiferroic properties were comparatively studied. The results indicate that all the synthesized composites mainly show bi-phase structure except slight presence of impurity phases. The surface of the specimens is relatively dense and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Typical hysteresis loops for ferroelectric materials were obtained for the pure BT80Zr20 ceramics. In the composites, the addition of ferromagnetic phase with higher conductivity influences the ferroelectric order in the materials, therefore the shape of these curves differs from the conventional ferroelectric materials and it is obviously influenced by the properties of magnetic phase [50]. Since the obtained loops are not well saturated it is very difficult to determine remnant polarization and coercive field with high accuracy.…”
Section: Sample T [°C]mentioning
confidence: 99%
“…Typical hysteresis loops for ferroelectric materials were obtained for the pure BT80Zr20 ceramics. In the composites, the addition of ferromagnetic phase with higher conductivity influences the ferroelectric order in the materials, therefore the shape of these curves differs from the conventional ferroelectric materials and it is obviously influenced by the properties of magnetic phase [50]. Since the obtained loops are not well saturated it is very difficult to determine remnant polarization and coercive field with high accuracy.…”
Section: Sample T [°C]mentioning
confidence: 99%
“…Multiferroic materials refer to materials with two or more orders of ferroelectric (antiferroelectric), ferromagnetic (antiferromagnetic) and ferroelastic [1][2][3]. Due to its unique ME coupling properties, multiferroic materials have some special physical properties, some meaningful and new physical phenomena are initiated [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Composite multiferroic materials take advantage of the ME coupling between two or more single-phase compounds without multiferroic properties, thus, the composite material with a good ME coupling effect is Z. Zeng et al / Processing and Application of Ceramics 14 [3] (2020) 223-230 formed. It was found that the ME coupling coefficient of composite materials was several times higher than that of single-phase materials [14][15][16].…”
Section: Introductionmentioning
confidence: 99%